2020
DOI: 10.3390/jcm9010262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Le Fort I Maxillary Advancement and Clockwise Rotation on the Anteromedial Cheek Soft Tissue Change in Patients with Skeletal Class III Pattern and Midface Deficiency: A 3D Imaging-Based Prediction Study

Abstract: Patients with a skeletal Class III deformity may present with a concave contour of the anteromedial cheek region. Le Fort I maxillary advancement and rotational movements correct the problem but information on the impact on the anteromedial cheek soft tissue change has been insufficient to date. This three-dimensional (3D) imaging-assisted study assessed the effect of surgical maxillary advancement and clockwise rotational movements on the anteromedial cheek soft tissue change. Two-week preoperative and 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
(100 reference statements)
2
10
1
3
Order By: Relevance
“…Similar to the present study, Foroughi et al reported no significant difference in NLA after maxillary advancement only based on cephalometric evaluation also, they trimmed the ANS in contrast to our study [ 26 ]. Conversely, Lai et al reported a significant increase in NLA after maxillary advancement and clockwise rotation and without trimming ANS similar to this study [ 33 ]. On the other hand, Nagori et al and Marsan et al reported a decrease in NLA by cephalometric evaluation after maxillary advancement [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the present study, Foroughi et al reported no significant difference in NLA after maxillary advancement only based on cephalometric evaluation also, they trimmed the ANS in contrast to our study [ 26 ]. Conversely, Lai et al reported a significant increase in NLA after maxillary advancement and clockwise rotation and without trimming ANS similar to this study [ 33 ]. On the other hand, Nagori et al and Marsan et al reported a decrease in NLA by cephalometric evaluation after maxillary advancement [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…To the best of our knowledge, no previous study has explored the difference in soft tissue changes after AMSDO between the cleft side and the noncleft side. In a previous study, the cheek soft tissue changes after cleft orthognathic surgery on the cleft was different from that on the noncleft side 16. However, we found no significant difference in the midfacial region on both sides.…”
Section: Discussioncontrasting
confidence: 78%
“…Ein Faktor von 1 entspricht dabei einer gleichwertigen Verlagerung von Weich-und Hartgewebe, während kleinere Werte eine geringere Veränderung des Weichgewebes gegenüber der knöchernen Basis bedeuten. Für sämtliche fazialen Regionen konnte in diesem Zusammenhang ein Verlagerungsfaktor von < 1 ermittelt werden, wobei die die größte Korrelation zwischen Hart-und Weichgewebsveränderung im Bereich des Kinns festgestellt werden konnte [11,12]. Konkret wurde im Bereich der Oberlippe ein Verlagerungsfaktor bei 0,78 und für die Unterlippe bei 0,77 beschrieben, hingegen für die Nasenspitze und -basis ein Wert von 0,74 bzw.…”
Section: Regionale Unterschiede Der Fazialen Weichgewebsreaktionunclassified
“…Konkret wurde im Bereich der Oberlippe ein Verlagerungsfaktor bei 0,78 und für die Unterlippe bei 0,77 beschrieben, hingegen für die Nasenspitze und -basis ein Wert von 0,74 bzw. 0,70 [12]. Für die Wangen ist ein Faktor von 0,73 und für das Kinn von 0,94 bekannt [11,12].…”
Section: Regionale Unterschiede Der Fazialen Weichgewebsreaktionunclassified
See 1 more Smart Citation